Morality and Spirituality in the Contemporary World - Chakrabarti, Chandana; Fairbanks, Sandra Jane. (Newcastle upon Tyne : Cambridge Scholars Pub., 2012)
The contemporary world faces a number of problems that are both deep-seated and interrelated, since they arise from the very nature of technological society. The environment upon which all life depends is seriously threatened by climate change, rising sea levels, pollution, overpopulation, resource depletion and increased risks of droughts, forest fires, floods and other extreme weather events. Environmental degradation is intimately connected to the consumer lifestyle of developed countries ...
TABLE OF CONTENTS; PREFACE; INTRODUCTION; CHAPTER ONE; CHAPTER TWO; CHAPTER THREE; CHAPTER FOUR; CHAPTER FIVE; CHAPTER SIX; CHAPTER SEVEN; CHAPTER EIGHT; CHAPTER NINE; CHAPTER TEN; CHAPTER ELEVEN; BIBLIOGRAPHY; CONTRIBUTORS.
Description based on print version record.
Keywords: Religious ethics; Spiritual life; Spirituality; Religious ethics; Spirituality; Spiritual life; RELIGION / Atheism; Electronic books